Epidemiology of Operative Procedures in an NCAA Division I Football Team Over 10 Seasons. Issue 7 (18th July 2016) - Mehran, Nima; Photopoulos, Christos D.; Narvy, Steven J.; Romano, Russ; Gamradt, Seth C.; Tibone, James E.
Background: Injury rates are high for collegiate football players. Few studies have evaluated the epidemiology of surgical procedures in National Collegiate Athletic Association (NCAA) Division I collegiate football players. Purpose: To determine the most common surgical procedures performed in collegiate football players over a 10-year period. Study Design: Descriptive epidemiological study. Methods: From the 2004-2005 season through the 2013-2014 season, all surgical procedures performed on athletes from a single NCAA Division I college football team during athletic participation were reviewed. Surgeries were categorized by anatomic location, and operative reports were used to obtain further surgical details. Data collected over this 10-season span included type of injury, primary procedures, reoperations, and cause of reoperation, all categorized by specific anatomic locations and position played. Results: From the 2004-2005 through the 2013-2014 seasons, 254 operations were performed on 207 players, averaging 25.4 surgical procedures per year. The majority of surgeries performed were orthopaedic procedures (92.1%, n = 234). However, there were multiple nonorthopaedic procedures (7.9%, n = 20). The most common procedure performed was arthroscopic shoulder labral repair (12.2%, n = 31). Partial meniscectomy (11.8%, n = 30), arthroscopic anterior cruciate ligament (ACL) reconstruction (9.4% n = 24), and arthroscopic hip labral repair (5.9% n = 15) were the other commonly performed procedures. There were a total of 29 reoperations performed; thus, 12.9% of primary procedures had a reoperation. The most common revision procedure was a revision open reduction internal fixation of stress fractures in the foot as a result of a symptomatic nonunion (33.33%, n = 4) and revision ACL reconstruction (12.5%, n = 3). By position, relative to the number of athletes at each position, linebackers (30.5%) and defensive linemen (29.1%) were the most likely to undergo surgery while kickers (6%) were the least likely. Conclusion: In NCAA Division I college football players, the most commonly performed surgeries conducted for injuries were orthopaedic in nature. Of these, arthroscopic shoulder labral repair was the most common, followed closely by partial meniscectomy. Nonorthopaedic procedures nonetheless accounted for a sizable portion of surgical volume. Familiarity with this injury and surgical spectrum is of utmost importance for the team physician treating these high-level contact athletes.